Analysis of Futsal Dribbling Ability of Students’ Extracurricular Participants at State Junior High School 1 Martapura - Ahmad Alvin Nizar; Ramadhan Arifin; Edwin Wahyu Dirgantoro (ACTIVE: Journal of Physical Education, Sport, Health and Recreation, 2025)
This study aims to analyze the dribbling skills of futsal extracurricular participants at state junior high school 1 Martapura. Dribbling is one of the fundamental techniques in futsal, essential for ball control, creating scoring opportunities, and supporting teamwork. The study employed a descriptive quantitative method, involving 15 students aged 13–15 selected through purposive sampling. Data were collected using a zig-zag dribbling test, with results categorized into five performance levels. The findings revealed that 3 students (20%) were in the “very good” category, 4 students (26.67%) in “good”, 1 student (6.67%) in “average”, 3 students (20%) in “poor”, and 4 students (26.67%) in the “very poor” category. These results indicate a significant disparity in dribbling abilities among the participants. The study concludes that most students still need improvement in their dribbling skills, which can be achieved through structured and consistent training programs. The findings are expected to serve as a basis for developing more effective futsal training methods within the school environment.